Toxic Waste Removal from Aqueous Solutions by Polyaniline: A Radiotracer Study - R.K. Gupta; Som Shankar (Adsorption Science & Technology)
A radiotracer technique was used to study the removal of Hg(II) ions from aqueous solutions by polyaniline. It was shown that an increase in the concentration of the adsorptive (10 −7 –10 −2 M), temperature (303–333 K) and pH (ca. 3–10) enhanced the removal of these ions. The first-order uptake of Hg(II) ions conformed to the Freundlich and Dubinin and Radushkevich (D–R) isotherms over the entire adsorptive concentration range (10 −7 –10 −2 M), whereas the Langmuir isotherm was followed only at moderate concentrations. Thermal data showed that this process was endothermic in nature. The radiation stability of polyaniline was also investigated by exposing it to an 11.1 GBq (Ra/Be) source associated with a γ-dose of 1.72 Gy/h. Irradiation had practically no significant effect on the adsorption capacity of polyaniline. Desorption experiments showed that the process of Hg(II) ion adsorption by polyaniline was almost irreversible and chemisorptive in nature.